The ethics knowledge among counsellors in Malaysia - Mat Rani, Nurul Hasyimah; Wan Jaafar, Wan Marzuki; Mohd Noah, Sidek; Ghazali, Mazila; Mahmud, Mohd Izwan (Malaysia Association of Research and Education for Educators, 2017)
Counsellor ethics is an important element in counsellor training. Ethics course is one of the compulsory courses in the counseling program as proposed by the Board of Counsellor, Malaysia. Ethics knowledge is able to help counsellors to behave ethically when practising counselling in an organisation. The aim of this study is to identify the knowledge pattern of counsellor ethics in Malaysia and the difference in the knowledge of counsellor ethics based on the demographic factors like age, gender, experience and counsellor’s qualification. This is a quantitative study using descriptive study design. A total of 355 counsellors had taken part in this study. The study instrument adopted is Ethical and Legal Issues in Counselling Questionnaires-Revised (ELICQ-R). The result of the score of the ethics knowledge of counsellor is at moderate and high level. The result also shows that there is a significant difference between counsellor qualification and the counsellors’ ethics knowledge in Malaysia. Other than that, there is no difference in the ethics knowledge based on the demographic factors like age, gender and the experiences of the counsellors in Malaysia. All in all, counsellors in Malaysia still have to increase their ethics knowledge so that they can deliver an effective counselling service to clients. The emphasis on ethics courses in the counseling program also has to be enhanced so that ethical counsellors can be produced in the future. Other than that, high ethics knowledge can help counsellors in behaving ethically.